Соціоніка як новий підхід в дослідженні законів комунікації інформаційних систем - Морушко, Олександр (Видавництво Львівської політехніки, 2016)
In theses proved the feasibility of using socionic analysis method when forming coherent team. An differences between socionics and psychology. Advantages socionic methods to psychological.
Keywords: collective psychology; socionics; compatibility; psychotypes; sociotypes